2016
DOI: 10.3390/ma9070579
|View full text |Cite
|
Sign up to set email alerts
|

Nb5+-Doped SrCoO3−δ Perovskites as Potential Cathodes for Solid-Oxide Fuel Cells

Abstract: SrCoO3−δ outperforms as cathode material in solid-oxide fuel cells (SOFC) when the three-dimensional (3C-type) perovskite structure is stabilized by the inclusion of highly-charged transition-metal ions at the octahedral positions. In a previous work we studied the Nb incorporation at the Co positions in the SrCo1−xNbxO3−δ system, in which the stabilization of a tetragonal P4/mmm perovskite superstructure was described for the x = 0.05 composition. In the present study we extend this investigation to the x = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
(37 reference statements)
2
20
1
Order By: Relevance
“…Yu et al, (2016) acknowledged the presence of small content of SrCO3 in the composite cathode are acceptable and has become stimulating phenomenal. There have been a few reliable studies evidence that the existence of a small amount of SrCO3 into SSC cathode is the reinforcement and assist in the increment of conductivity throughout the electrochemical performance of low temperature solid oxide fuel cell (LTSOFC) [17,20]. It is depicted in Fig.…”
Section: Results and Discussion 31 Phase Formation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al, (2016) acknowledged the presence of small content of SrCO3 in the composite cathode are acceptable and has become stimulating phenomenal. There have been a few reliable studies evidence that the existence of a small amount of SrCO3 into SSC cathode is the reinforcement and assist in the increment of conductivity throughout the electrochemical performance of low temperature solid oxide fuel cell (LTSOFC) [17,20]. It is depicted in Fig.…”
Section: Results and Discussion 31 Phase Formation Analysismentioning
confidence: 99%
“…However, other researchers revealed that the incorporation of a small amount of SrCO3, as additional phase into the cathode system resulted in an enhancement of ORR value due to the improvement of surface exchange coefficient and electrochemical performance typically at intermediate temperature [17].The fundamental clarification on the influence of the secondary phase in terms of the microstructural and physical properties towards new cathode of SSC-SDCC needs to be investigated in detail. Therefore, systematic research has to be thoroughly conducted to clarify the influence of secondary phase on the structural and electrochemical characterization of SSC based composite cathode.…”
Section: Introductionmentioning
confidence: 96%
“…Whereas the cubic phase exhibits an excellent ionic and electronic conductivity, the hexagonal phase has very poor properties and, unfortunately, it is thermodynamically stable, which limits the use of this pure material as a cathode in SOFC. As a strategy to prevent this cubic-to-hexagonal phase transition, it was found that replacing few percentages of Co by aliovalent elements like Re, Nb, Sb or Ti was effective to stabilize the cubic phase in a wide temperature range [9,10,11,12,13]. Recently, we observed that replacing 5% of Co by Ru prevents this unwanted transformation and enhances the catalytic oxygen reduction reaction [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, there are several articles analyzing the effect of partial substitutions of cobalt by Ti showing that these ions promote the stabilization of a tetragonal superstructure and cubic phase, respectively. However, these materials were synthesized by methods that employed high temperatures, generating crystallite sizes on a micrometric scale [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric analyses were carried out to determine the oxygen vacancies () in the samples with a Shimadzu DTG-60 device in air flow up to 900 °C, using a heating rate of 10 ºC/min with -alumina as reference and crucible material[21,25].…”
mentioning
confidence: 99%